Geologic materials and gamma radiation in the built environment - Sanjurjo-Sánchez, Jorge (2017)
Human exposure to natural ionizing radiation is due to both internal sources such as ingestion and inhalation of radioactive isotopes, and external sources from cosmic radiation and primordial radionuclides present in the Earth crust. Primordial radionuclides are K-40 and radioisotopes of the decay series of U-238 and Th-232, which emit gamma radiation at low doses. Gamma emission can occur both in outdoor, due to background geologic radiation, and in indoor spaces, due to the use of geologic materials in dwellings. This radiation has received less attention than man-made sources because it contributes less to the total doses that affect humans, on the average. However, there are geographical areas and rocks used as building materials that contain high concentrations of radionuclides, thus being a source of relatively high gamma dose exposures. Assessing exposure is difficult, especially in indoor situations where there are marked variations regarding materials application. Nonetheless, some measures and regulations to control such dose exposures on building materials have been suggested. This article reviews gamma radiation in geologic materials used for buildings. We discuss: (1) procedures that relate radionuclide contents in building materials to external gamma radiation, considering namely indoor applications and that are used for establishing restrictions on building materials commerce; (2) relation of rock radionuclide contents with their geologic history that can lead to listing of some geologic materials as potentially hazardous in terms of gamma radiation; and (3) the implications for the European regulation, which has an universal criteria that might be excessively restrictive for the commerce of geologic materials used in small amounts, and does not have provisions regarding existing structures where geologic materials are used in extended amounts.